2020
DOI: 10.1002/chem.202001259
|View full text |Cite
|
Sign up to set email alerts
|

Visible Light‐Enabled sp3‐C−H Functionalization with Chloro‐ and Bromoalkynes: Chemoselective Route to Vinylchlorides or Alkynes

Abstract: An unprecedented direct atom‐economic chemo‐ and regioselective hydroalkylation of chloroalkynes and an sp3‐C−H alkynylation of bromoalkynes was achieved. The reaction partners are unfunctionalized ethers, alcohols, amides, and even non‐activated hydrocarbons. We found that a household fluorescent bulb was able to excite a diaryl ketone, which then selectively abstracts a H‐atom from an sp3‐C−H bond. The product of a formal alkyne insertion into the sp3‐C−H bond was obtained with chloroalkynes, providing valua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
18
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 126 publications
0
18
0
Order By: Relevance
“…At the time of writing, Hashmi and co-workers reported the visible light-photocatalyzed hydroalkylation of chloroalkynes. 19 Thus, we started wondering about the role of the radicofugal group in the present methodology and reacted compounds 2m – r (see Chart S1 ) with 1a under optimized conditions. We found that only sulfonyl alkynes gave product 3 in good yields ( Scheme 4 a; reactivity order: 2a > 2n > 2m ), while the well-known benziodoxolone-based alkynylating reagent ( 2o , see Chart S1 ) proved to be photochemically unstable under our conditions and 3 was formed only in a poor yield (17%, data not shown).…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…At the time of writing, Hashmi and co-workers reported the visible light-photocatalyzed hydroalkylation of chloroalkynes. 19 Thus, we started wondering about the role of the radicofugal group in the present methodology and reacted compounds 2m – r (see Chart S1 ) with 1a under optimized conditions. We found that only sulfonyl alkynes gave product 3 in good yields ( Scheme 4 a; reactivity order: 2a > 2n > 2m ), while the well-known benziodoxolone-based alkynylating reagent ( 2o , see Chart S1 ) proved to be photochemically unstable under our conditions and 3 was formed only in a poor yield (17%, data not shown).…”
mentioning
confidence: 99%
“…Turning to halogenated derivatives, while (iodoethynyl)benzene ( 2p ) and (bromoethynyl)benzene ( 2q ) were recovered unreacted, chloroalkyne 2r led to the formation of product 31 only (41% isolated yield, Z isomer; Scheme 4 b), in accordance with the report by Hashmi. 19 Intrigued by this marked difference in reactivity, we undertook a computational analysis based on density functional theory (DFT; UωB97xD/def2tzvp level of theory in the gas phase) and compared the aptitude of the different RSO 2 • moieties vs Cl • in the role of radicofugal groups ( Table S2 ). In particular, the equation reported in Scheme 4 c compares the tendency of MeSO 2 and Cl to stabilize the vinyl radical adduct with respect to their intrinsic stability as free radicals.…”
mentioning
confidence: 99%
See 3 more Smart Citations